Etiologies and prognostic factors of leukocytoclastic vasculitis with skin involvement: A retrospective study in 112 patients. Issue 28 (July 2016) - Bouiller, Kévin; Audia, Sylvain; Devilliers, Hervé; Collet, Evelyne; Aubriot, Marie Hélène; Leguy-Seguin, Vanessa; Berthier, Sabine; Bonniaud, Philippe; Chavanet, Pascal; Besancenot, Jean-François; Vabres, Pierre; Martin, Laurent; et al.
Abstract : Abstract: In this study, outcomes of patients with leukocytoclastic vasculitis (LCV) were analyzed focusing on clinical, histopathology and laboratory findings, relapses, and survival. Data from patients with cutaneous vasculitis diagnosed between January 1, 2000, and December 31, 2010, at Dijon University Hospital (France) were retrospectively reviewed. LCV was defined as perivascular neutrophilic infiltrate, endothelial cell nuclear swelling, extravasation of red blood cells, and/or fibrin deposition in vessels. Patients were classified according to the 2012 Chapel Hill Consensus Conference. Relapses were defined as the recurrence of vasculitis symptoms after a period of remission >1 month. Time to relapse and/or death was calculated from the date of diagnosis. Univariate and multivariate (Cox model) analyses were performed. A total of 112 patients (57 males and 55 females), with a mean age of 60 ± 19 (18–98) years, were analyzed. Overall follow-up was 61 ± 38 months. At diagnosis, all patients had skin lesions, purpura being the most common (n = 83). Lesions were associated with systemic involvement in 55 (51%) patients. Only 41 (36.6%) patients received specific treatment: glucocorticoids in 29 of 41 (70.7%) and immunosuppressants in 9 of 41 (22%). Sixty-two patients (55%) had LCV due to underlying causes, 29 (25.9%) had single-organ cutaneous small vessel vasculitis (SoCSVV), and 21 (18.8%) had unclassifiable LCV. Twenty patients of the cohort (18%) experienced relapse, 14 ± 13 (1–40) months after the diagnosis of LCV. None of the 29 patients with SoCSVV relapsed. Independent risk factors for relapse were vascular thrombosis in the biopsy [hazard ratio (HR) = 4.9; P = 0.017], peripheral neuropathy (HR = 9.8; P = 0.001), hepatitis (HR = 3.1; P = 0.004), and positive antineutrophil cytoplasm antibodies (ANCA, HR = 5.9 P = 0.005). In contrast, SoCSVV was a protective factor for relapse (HR = 0.12; P = 0.043). The 1-, 3-, and 6-year overall survival rates were 99%, 83%, and 71%, respectively, with no difference between relapsers and nonrelapsers ( P = 0.960) or between SoCSVV and unclassifiable LCV ( P = 0.588). This study demonstrates that global survival for LCV patients is good but relapses remain frequent, especially when the cutaneous biopsy shows vascular thrombosis, or in patients with peripheral neuropathy or hepatitis. Conversely, SoCSVV is a protective factor for relapse.